The Potential of Sunflower Seed Biscuits in Lowering Blood Glucose and Malondialdehyde Level in Type 2 Diabetes Mellitus Rat Models - Pratiwi, Emilia Arum; Juniarto, Achmad Zulfa; Afifah, Diana Nur (Universitas Airlangga, 2024)
Type 2 diabetes mellitus (T2DM) is marked by early hyperglycemic symptoms and concurrent insulin resistance, leading to insulin secretion dysregulation. This resistance correlates with heightened Reactive Oxygen Species (ROS) level and reduced malondialdehyde. T2DM elevates malondialdehyde, necessitating antioxidant-rich interventions. Sunflower seed biscuits serve as a rich source of enzymatic antioxidants. The primary objective of this investigation was to substantiate the capacity of sunflower seed biscuits to ameliorate blood glucose and malondialdehyde level in T2DM-afflicted rats. Sunflower seed biscuits were investigated for their impact on blood glucose and malondialdehyde in 24 male Wistar rats. Rats were divided into four groups: diabetes rats (K-), simvastatin-treated (K+), receiving 0.72 g sunflower seed biscuits per rat body weight (X1), and 1.44 g (X2). Administered for 28 days via oral gavage, T2DM was induced through a high-fat diet and streptozotocin. Results showed significant blood glucose reduction in treatment groups (X1: 3.99 ng/mL, X2: 2.89 ng/mL) vs. controls (9.8 ng/mL), with statistical significance (p<0.05). Sunflower seed biscuits effectively lowered blood glucose and malondialdehyde in T2DM rats. The X2 group exhibited superior efficacy in reducing both parameters. Thus, sunflower seed biscuits present promise as a viable dietary option for T2DM management.